A case report on osler-weber-rendu disease (Indian Journal of Case Reports, 2019)
Osler-Weber-Rendu disease, also known as hereditary hemorrhagic telangiectasia (HHT) is a rare autosomal dominant genetic disorder that leads to abnormal blood vessel formation in the skin, mucous membrane and in organs such as lungs, liver, and brain. Here, we report the case of a 68-year-old postmenopausal woman who was admitted to our hospital following multiple episodes of hematemesis and melena during the past 5 days. Upper GI endoscopy revealed multiple telangiectasia with active spurting and gastric polyp. The patient was treated with 1 unit of packed red blood cells transfusion for anemia, Inj. Tranexamic acid 500 mg IV tid and Inj. Ondansetron 4 mg IV for hematemesis. Tab. Thalidomide 100 mg has been given for treating hereditary hemorrhagic telangiectasia. The treatment of HHT is only palliative, with no consensus on the best treatment option. It is essential to promote control of the disease as long as possible.